(untitled) - World Health Organization (Rome, 2007)
The codex Alimentarius is the result of the commissions work: a collection of international adopted food standards, guidelines, codes of practice and other recommendations,..
Keywords: Food,Food industry and trade,Thực phẩm,Công nghiệp thực phẩm và thương mại; Standards,Standards,Tiêu chuẩn,Tiêu chuẩn